Advanced gastric cancer with features of a submucosal tumor diagnosed by endoscopic ultrasound-guided fine needle aspiration and boring biopsy preoperatively: A case report and literature review. (2019) - Yamane, Hiroaki; Ishida, Michihiro; Banzai, Seisyu; Kubota, Tetsushi; Miyake, Soichiro; Choda, Yasuhiro; Idani, Hitoshi; Shiozaki, Shigehiro; Okajima, Masazumi
Highlights: Gastric carcinoma with features of a submucosal tumor is a rare condition. Gastric carcinoma with features of a submucosal tumor has unique features. Tissue sampling must be performed if gastric malignant submucosal tumor is suspected. Abstract: Introduction: Gastric cancer with features of a submucosal tumor (GCSMT) is rare, and the preoperative diagnosis is very difficult. We present a case of GCSMT diagnosed by endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) and boring biopsy (deeper biopsy), successfully treated with distal gastrectomy and lymph node dissection. Presentation of case: An 81-year-old man with a history of myocardial infarction and type 2 diabetes mellitus was admitted to our hospital for further examination of a gastric submucosal tumor. Endoscopic examination of the gastrointestinal tract showed a 30-mm submucosal tumor at the lower gastric body. Enhanced computed tomography revealed a tumor located at the lower body of the stomach and pyloric lymph node swelling. EUS-FNA and boring biopsy from the tumor revealed adenocarcinoma. Accordingly, distal gastrectomy with lymph node dissection was performed. Histopathological examination showed a poorly differentiated adenocarcinoma. Postoperative diagnosis was GCSMT with lymph node metastasis (T2, N1, M0, stage IIA). Conclusion: We report a rare case of GCSMT with lymph node metastasis. Preoperative diagnosis of GCSMT is necessary to guide surgical management. EUS-FNA and boring biopsy could aid in obtaining adequate quantities of the specimens for histopathological and immunohistochemical diagnosis.